CTF development, verification, and validation for VVER core thermal-hydraulics and multi-physics modeling and simulation - Kutlu, Yesim; Spasov, Ivan; Mitkov, Svetlomir; Rouxelin, Pascal; Abarca, Agustin; Kolev, Nikola; Avramova, Maria; Ivanov, Kostadin (Frontiers in Nuclear Engineering, 2025)
The advanced thermal-hydraulics sub-channel tool CTF has been in the process of continuous development and improvement by Oak Ridge National Laboratory (ORNL) and North Carolina State University (NCSU). In recent years, there has been considerable progress in code development, including new functionalities, application-specific correlations, various multi-physics applications, built-in pre- and post-processors, improved solvers, parallelization, and extensive testing. VVER applications are part of these activities. NCSU has been cooperating with the Institute for Nuclear Research and Energy (INRNE) on CTF development, verification, and validation for VVER core modeling and simulation. This article presents an overview of these CTF studies for VVER applications. Several test cases are considered, which include pure thermal-hydraulic problems as well as multi-physics simulations at the nodal and pin level. On the single physics side, thermal-hydraulic CTF solutions have been compared against measured data for rod bundle, fuel assembly, and full core, as well as code-to-code vs. FLICA4 solutions. CTF was tested in the simulation of the TVSA-5T VVER mini-assembly experiments and in the full-core steady-state calculation for the ongoing OECD/NEA Rostov-2 benchmark. For the TVSA-5T calculations, CTF was coupled with the uncertainty analysis tool Dakota and utilized to propagate uncertainties of input and boundary conditions to output quantities of interest for thermal-hydraulic parameter investigations. The CTF results and measured data obtained from this experimental setup were compared for validation. To produce reliable pin-resolved reference solutions for multi-physics model testing the high-fidelity continuous energy Monte Carlo-based neutron transport codes MCNP6.2 and Serpent 2.2.0 were separately coupled with the CTF sub-channel code. Coupled models of a VVER-1000 fuel assembly were tested in comparisons between MCNP/CTF and Serpent/CTF results. Coarse-mesh multi-physics solutions for a full core have been obtained with the coupled COBAYA/CTF, COBAYA/FLICA4, and PARCS/CTF codes. These solutions have been compared against steady-state plant data and code-to-code for transients. High-fidelity pin-resolved solutions with SERPENT/CTF serve as reference solutions in a steady state. The outcomes from the various studies of single-physics and multi-physics cases used for CTF verification and validation met the initial expectations both qualitatively and quantitatively. The results of the numerical verification and experimental validation are in good agreement with the corresponding reference data.